Green transformational leadership and employee organizational citizenship behavior for the environment in the manufacturing industry: A social information processing perspective - Liu, Xuhong; Yu, Xuan (Frontiers in Psychology, 2023)
The environmental improvement of an organization largely depends on the green behavior of employees. Drawing on the theory of social information processing, this study takes a sample of 312 managers to discuss the influencing mechanism of green transformational leadership affecting the employee organizational citizenship behavior for the environment (OCBE) in the manufacturing industry. The results show that: green transformational leadership has a significant positive impact on employee OCBE, and green organizational climate has a mediating effect on the impact of green transformational leadership on employee OCBE. Furthermore, environmental concern not only has a positive moderating effect on the influence of green transformational leadership on green organizational climate, but also positively moderates the impact of the influence of green transformational leadership on employee OCBE.